Modelling and Calculation of Raw Material Industry - Czajka, Krzysztof; Kawalec, Witold; Król, Robert; Sówka, Izabela (2022)
The raw materials industry is widely considered to be too environmentally costly, and causing more losses than benefits. The responsible solving of the problems caused by this industry is not "exporting" its operations to less developed countries, but addressing all recognized hazards with dedicated technological developments. Such an approach is presented by the authors of this book. The contributions deal with the optimization of processes in the raw materials industry, obtaining energy from alternative fuels, researching the environmental aspects of industrial activities. This book determines some guidelines for the sustainable raw materials industry, describing methods of the optimized use of mined deposits and the recovery of materials, reductions in energy consumption and the recuperation of energy, minimizations in the emissions of pollutants, the perfection of quieter and safer processes, and the facilitation of modern materials-, water-, and energy-related techniques and technologies.